Biotechnology, viral oncogenesis and jaagsiekte - Verwoerd, D W (Onderstepoort journal of veterinary research, 1985)
A brief description is given of the discovery of retroviral and cellular oncogenes and of their putative role in oncogenesis. Attempts to apply the biotechnological techniques that were so successful in the study of other retroviruses to the newly-discovered jaagsiekte retrovirus are briefly reviewed.